HILITE—ions in intense photon fields. (26th November 2015) - Ringleb, S; Vogel, M; Kumar, Sugam; Quint, W; Paulus, G G; Stöhlker, Th
Abstract: We are currently devising the open-endcap Penning trap experiment (high-intensity laser ion-trap experiment) as a tool for ion confinement, manipulation and detection to be used at high-energy and/or high-intensity laser facilities. This instrument will allow studies of laser–ion interactions with well-defined ion targets, and to detect the reaction products non-destructively. The ion target may be controlled concerning the constituent species, the density, shape and position with respect to the laser focus. For commissioning experiments, we optimize the focusing parameters to achieve a high number of ionized particles per shot. The detection electronics is designed to measure all charge states of all nuclei up to xenon. We plan first experiments with argon and xenon irradiated by a titanium:sapphire chirped-pulse-amplification laser system with 10 mJ pulse energy and a pulse duration of 30 fs.